Magnetic-Field-Assisted Electric-Field-Induced Domain Switching of a Magnetic Single Domain in a Multiferroic/Magnetoelectric Ni Nanochevron/[Pb(Mg1/3Nb2/3)O3]0.68–[PbTiO3]0.32 (PMN–PT) Layered Structure - Chih-Cheng Cheng; Yu-Jen Chen; Shin-Hung Lin; Hsin-Min Wang; Guang-Ping Lin; Tien-Kan Chung (Micromachines, 2023)
We report the magnetic-field-assisted electric-field-controlled domain switching of a magnetic single domain in a multiferroic/magnetoelectric Ni nanochevrons/[Pb(Mg1/3Nb2/3)O3]0.68–[PbTiO3]0.32 (PMN–PT) layered structure. Initially, a magnetic field was applied in the transverse direction across single-domain Ni nanochevrons to transform each of them into a two-domain state. Subsequently, an electric field was applied to the layered structure, exerting the converse magnetoelectric effect to transform/release the two-domain Ni nanochevrons into one of two possible single-domain states. Finally, the experimental results showed that approximately 50% of the single-domain Ni nanochevrons were switched permanently after applying our approach (i.e., the magnetization direction was permanently rotated by 180 degrees). These results mark important advancements for future nanoelectromagnetic systems.